The impact of Catena-X on digital business models in the automotive industry - Ehlers, Leon (2023)
Like many other manufacturing industries, the automotive industry is also affected by the consequences of the climate crisis and is required to ensure greater sustainability. Corresponding laws and standards are continuously coming into force and require new methods of implementation. A shared network that supports standardized verification and facilitates communication among participants is the industry's answer. Promoted by the German government, the expectation is to better equip the industry for an increasingly digital, global market. The emergence of open data ecosystems such as Catena-X in the automotive industry creates new opportunities for value creation by extending existing, or creating new Business Models. Catena-X is an open data ecosystem that connects the supply chain and creates value through increased transparency, which in turn leads to sustainability in the industry. Companies that are part of the automotive supply chain can thereby profitably contribute their data, creating benefits for the entire network. The research in this thesis is based on five semi-structured interviews with experts from the German automotive industry. The responses enable the identification of current developments, including the merging of production and service as a Business Model, but also a transformation of smaller companies that are adapting to the digital age in order to benefit from the new opportunities for value creation. This study places itself in a comparatively early phase of Catena-X and shows possible paths for further research, especially with regard to sustainability, which provides a solid basis for value creation on a social, environmental, and economic level.